THE INFLUENCE OF AUTHENTICITY ON TOURIST LOYALTY AT LAUT TAWAR LAKE - Ahmad Jajuli; Syaifuddin Syaifuddin; Sofiyan Sofiyan (Journal of Information Systems Management and Digital Business, 2026)
Tourism destination management is crucial for ensuring visitors feel comfortable and are interested in returning. This study aims to analyze the influence of authenticity on tourist loyalty. The analysis method used is Structural Equation Modeling (SEM) using SmartPLS. The sample was calculated using the Slovin formula, resulting in 470 respondents. The analysis results show that authenticity also has a direct influence on tourist loyalty (Y), with positive coefficients of 0.195, 0.219, and 0.196, respectively. Overall, these findings contribute to the understanding of the influence of digital and cultural elements on tourist loyalty and emphasize the important role of social media in influencing tourist decisions. In addition, the authenticity of a tourist area must be maintained to ensure loyal tourists return to Lake Lau Kawar.